Animated painting of Saint-Ouen (tableau anime), France, 1759, wood... - Daderot (Wikimedia Commons, 2020)
Notice iconographique issue de Wikimedia Commons. Titre: Animated painting of Saint-Ouen (tableau anime), France, 1759, wood, glass, leather, tin, iron alloy, brass - Metropolitan Museum of Art - New York City - DSC07124. Exhibit in the Metropolitan Museum of Art - New York City, New York, USA.
Droits : Licence Public domain via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons; Peintures